A coesão textual em narrativas de alunos do 7° ano do ensino fundamental - Matei, Maria Helena Corrêa da Silva (2012)
This dissertation is linked to a line of research Leitura, Escrita e Ensino of the Program of Post Graduation in the Portuguese Language of the Pontifícia Universidade Católica de São Paulo. Having in mind the Learning Expectations present in the Pedagogic Project of two public schools in the East Metropolitan Area of the city of São Paulo, at the first place, it has been checked the models used by the students to build up the semantic relations responsible for the cohesion of their texts. Immediately after that, it has been defined, in the production of the text of these students the resources that present inadequacies and to close, it has been checked whether the students of the 7th grade of the secondary school of these schools have established the cohesion in the adequate form in the school years that correspond to their age group (11-13 years old). For the examination, it has been opted for genre short stories, as it has been contemplated in the schools since the first grade. The choice has been based in the hypotheses that is easier to analyse the student s writing, when using textual outputs, which structure is or should be familiar to their authors. For that, it has been adopted the concept of text advocated by Beaugrande (1997): communicative event where the actions of linguist order, cognitive and socials, are related. From those actions, it has been highlighted the ones of linguist order and prioritization has been given to the concepts of cohesion proposed by Fávero (2010), who conceives cohesion in a level different from the one of the coherence. The analyse has shown us that the strategy of the cohesion are presented in the productions. However, the students from one school, as well as the students from the other one, have shown certain cohesive inabilities in relation to what is expected from them at the end of school years spent in the secondary school, considering that the Learning Expectation orient the teaching of the Portuguese language in the Municipal schools of the city of São Paulo